Analisis Yuridis mengenai Diversi sebagai Bentuk Penyelesaian Perkara Pidana Anak dalam Pendekatan Restorative Justice - Toman Febriandi Sibuea; Setiyono Setiyono (Postgraduate University of Merdeka Malang, 2023)
Children who are legal subjects and national assets, as part of the younger generation, children play a strategic role as the next generation of the nation, because this strategic role has been realized by the international community to give birth to a convention which essentially emphasizes the position of children as human beings who must receive protection for their rights. -his rights. The awareness to make criminal justice the last step in dealing with children in conflict with the law is reflected in the conventions agreed upon by countries in the world. But seeing the reality, the resolution of cases committed by children is still the same as adults, namely through the judicial process. The results will stamp the child as a convict who is worried that this situation will have a negative impact that can affect the mental and soul of the child. The formulation of the problem in this study is 1. What is the juridical analysis of Diversion as a form of solving juvenile criminal cases in the Restorative Justice approach? ? 2. Is the Diversion arrangement with the Restorative Justice approach appropriate to be applied in Crimes committed by children in Indonesia? The research method used is Normative Juridical Legal Research.First, The Restorative Justice approach can be seen from the various legal arrangements set forth in both national and international regulations. Second, Restorative Justice arrangements for crimes committed by children according to researchers are appropriate, with the existence of diversion and restorative justice it is hoped that they can provide support for the process of protecting children who are in conflict with the law. This is because the main principle of diversion and restorative justice is to prevent perpetrators of criminal acts from the formal criminal justice system and to provide opportunities for perpetrators to carry out alternative sanctions without imprisonment. Diversion is closely related to the concept of restorative justice, and can be applied if a naughty child is willing to admit his mistake, while at the same time giving the child the opportunity to correct his mistake. Diversion is a good form of intervention in changing the behavior of naughty children, with the involvement of the family, community and police, the child can understand the impact of his actions.